Taxonomía de algunos microtéidos de Venezuela (Squamata), H: Situación nomenclatural de Prionodactylus ampuedai y Prionodactylus phelpsorum - Mijares-Urrutia, Abraham (Revista de Biología Tropical, 2000)
New records of the poorly known microteiid lízard Prionodactylus ampuedai, morphological variation, and new data on natural history are reported. We report the loss of the holotypes of P. ampuedai and P. phelpsorum, and designate a neotype for the former. Euspondylus goeleti is resurrected from the synonymy with E. phelpsorum and this lalter is transferred to the genus Priollodactylus